Дослiдження протяжних плазмово-пилових структур - Golovanov, A. I.; Podryadchikov, S. F.; Scherbina, A. I. (Publishing house "Academperiodika", 2018)
We continue to produce and to grow dusty plasma structures in a DC glow discharge plasma. The size of dusty plasma structures is comparable to the size of the positive column. The previous studies have shown that the such dusty plasma structures can involve over 10^6 particles.